Peristomal pyoderma gangrenosum successfully treated with cyclosporine - Urano, Shoko; Abe, Jinnroh; Kikuchi, Hirotoshi (Trends in Immunotherapy, 2022)
Peristomal pyoderma gangrenosum (PPG) is an uncommon subtype of pyoderma gangrenosum. We describe a 74-year-old woman without inflammatory bowel disease (IBD) who developed PG around the jejunostomy and was successfully treated with cyclosporine. In our case, irritations by a lumbar corset and repeated sutures around the jejunostomy seemed to have caused pathergy reaction. It is noteworthy that 20% of PPG patients do not have IBD and therefore patients presenting PPG without IBD should not be overlooked.